A new species of Parahyparrhenia (Poaceae: Andropogoneae) from India - Tiwari, Arjun Prasad; Chorghe, Alok R.; Landge, Shahid Nawaz; Mujaffar, Shaikh (Phytotaxa, 2020)
Parahyparrhenia khannae, a new species of Andropogoneae (Poaceae: Andropogoneae) from the grassland of Ratlam and Jhabua districts of Madhya Pradesh, India is described and illustrated. The new species is similar to the Indian endemic species P. bellariensis in having dorsal groove in lower glume of sessile spikelet, but differs in having shorter plant height, lacerate membranous ligule, shorter leaf blade and raceme length, fewer homogamous spikelets, shorter sessile spikelet and anther length.